UNIT 12.37 Light Sheet Fluorescence Microscopy (LSFM). Issue 1 (5th January 2015) - Adams, Michael W.; Loftus, Andrew F.; Dunn, Sarah E.; Joens, Matthew S.; Fitzpatrick, James A.J.
Abstract : The development of confocal microscopy techniques introduced the ability to optically section fluorescent samples in the axial dimension, perpendicular to the image plane. These approaches, via the placement of a pinhole in the conjugate image plane, provided superior resolution in the axial (z) dimension resulting in nearly isotropic optical sections. However, increased axial resolution, via pinhole optics, comes at the cost of both speed and excitation efficiency. Light sheet fluorescent microscopy (LSFM), a century‐old idea made possible with modern developments in both excitation and detection optics, provides sub‐cellular resolution and optical sectioning capabilities without compromising speed or excitation efficiency. Over the past decade, several variations of LSFM have been implemented each with its own benefits and deficiencies. Here we discuss LSFM fundamentals and outline the basic principles of several major light‐sheet‐based imaging modalities (SPIM, inverted SPIM, multi‐view SPIM, Bessel beam SPIM, and stimulated emission depletion SPIM) while considering their biological relevance in terms of intrusiveness, temporal resolution, and sample requirements. © 2015 by John Wiley & Sons, Inc.